Peran Milenial dalam Digital Ecotourism di Era Society 5.0 - Sri Wahyu Lelly Hana Setyanti; Sudarsih Sudarsih (Jurnal Akuntansi dan Pajak, 2023)
The progress of science and technology triggered the era of society 5.0, which gave birth to changes in responding to future needs. In the era of Society 5.0, the main component is humans who can create new value through technological developments. Digitization of ecotourism can be in the form of information providers, technology applications for booking tickets, hotels and other accommodations. This digital transformation of ecotourism encourages millennials to combine cyber technology with automation. This study analyzes millennials' role and challenges in digital ecotourism in the era of society 5.0.